Rupture, Invasion and Inflammatory Destruction of the Intestinal Barrier by Shigella: The Yin and Yang of Innate Immunity - Philippe J Sansonetti (Canadian Journal of Infectious Diseases and Medical Microbiology, 2006)
Shigella is a Gram-negative bacterial species of the family Enterobacteriaceae that causes bacillary dysentery in humans. This acute colitis reflects the capacity of the microorganism to disrupt, invade and cause the inflammatory destruction of the intestinal epithelium. The pathogenesis of the Shigella infection can be seen as a disruption of the homeostatic balance that protects the gut against inflammation in the presence of its commensal flora. This provides the unified view that enteroinvasive pathogens allow for the identification of key signalling molecules and pathways involved in the regulation of intestinal inflammation, and more generally, in the regulation of the innate and adaptive immune response.